Work Ethics and Organizational Performance in The Nigerian Public Service: A Study of Delta and Rivers States, Nigeria - Nwachuku, Azuka; Okereka, Onofere Princewill; Mukoro, Akpomuvire (ARISTO, 2026)
This study examined the impact of work ethics on organizational performance in the public service sectors of Delta and Rivers states. Using a cross-sectional research design, data were collected through a structured survey from a sample of 506 employees randomly selected from both states. The study was grounded in labour process theory and agency theory. Labour process theory highlights how organizations can limit employee autonomy by implementing control mechanisms to enhance work performance. Meanwhile, agency theory emphasizes the use of decision-making rights to ensure effective governance, management, and the establishment of incentives and sanctions within an organization. A systematic random sampling method was used to select survey respondents, and the data were analyzed using Pearson’s product-moment correlation and multiple regression analysis. The findings revealed that work ethics encompassing work attitude, workplace commitment, teamwork, and workplace discipline, had a significant and positive impact on organizational performance in the public services of Delta and Rivers states. Additionally, the study identified a linear positive relationship between work ethics practices and organizational performance. This indicates that work ethics not only hold sentimental value but are also critical for enhancing public service performance and sustaining service delivery in Nigeria. The study concluded that work ethics positively influence organizational performance in Delta and Rivers states' public service. The ethical principles outlined in the Nigerian public service code play a key role in guiding civil servants towards behaviors that improve organizational outcomes. As a recommendation, leaders in the public service of Delta and Rivers states, as well as across Nigeria, should prioritize staff training on workplace ethics. Such efforts would help improve employee attitudes, commitment, teamwork, and discipline, ultimately fostering better performance amidst evolving workplace dynamics. The study was limited to the public service sectors in Delta and Rivers states. It is recommended that future research expand to include other states across Nigeria to provide a more comprehensive understanding of the topic.